Pertumbuhan Populasi dan Oviposisi Wereng Hijau, Nephotettix virescens Distant (Hemiptera: Cicadellidae) Berkaitan dengan Saat Padi Keluar Malai - I Nyoman Widiarta (Universitas Gadjah Mada, 1996)
Effects of early and late-maturing varieties of rice on the population growth of N. virescens was investigated during the wet season crop of 1994/1995, and dry season crop of 1995 in the experimental fields of Research lnstitute for Rice in Sukamandi. A pot experiment to observe oviposition rate of N. virescens on both varieties was conducted in screen house in the dry season crop of 1995. The population fluctuation of N. virescens on both varieties as well as number of eggs of the first generation at 8 weeks after transplanting were similar. The population density increased during early growth stage of rice from immigrant generation to the first generation and decreased thereafter. The peak emergence of adults of the first generation on early maturing variety occured after the flowering stage, on the otherhand on late maturing variety the peak emergence of adults occured before the flowering stage. Adult N. virescens laid more eggs on early maturing variety after flowering stage than that on late maturing variety before flowering stage (p< 0.01; t-test) in the pot experiment. Those field and pot experiment facts indicated that the first generation of adult emigrant influenced the population fluctuation in the fields, because the density of predator, Lycosa, was lower in the early maturing variety than in the late maturing variety in the wet season crop of 1994/1995 and it was similar in the dry season crop of 1995.